Development And Evaluation Of Online Cognitive Diagnostic Assessment With Feedback On The Concept Of Time In Year Four And Five Mathematics - Chin, Huan (2020)
Time is a difficult mathematical concept for Year Four and Five pupils. This study aimed to develop and evaluate an online Cognitive Diagnostic Assessment (CDA) with feedback for assessing Year Four and Five pupils’ achievement in the topic of ‘Time’. The development of the online CDA with feedback was conducted in the first phase of the study while the evaluation of the online CDA with feedback was conducted in the second phase of the study. Multimethod research design was employed in the study. The 28 Year Four expert-based cognitive models and 21 Year Five expert-based cognitive models were specified by mathematics education experts and judged to be valid by six subject matter experts from National School (SK), National-Type Chinese School (SJKC) and National-Type Tamil School (SJKT) respectively, in terms of (a) relevance of the attributes to Year Four and Year Five Mathematics content and learning standards; and (b) hierarchical arrangement of attributes. The 28 Year Four construct maps and 21 Year Five construct maps derived from the expert-based cognitive models were then judged to be valid by the same panel of subject matter experts. The contents of the online CDA with Ordered Multiple- Choice (OMC) items in Malay, Mandarin and Tamil respectively were also judged to be valid by the subject matter experts in terms of: (a) classification of attributes based on the revised Bloom’s Taxonomy with simple percent agreement of 100 percent; (b) relevance of the items to the attributes intended to be measured with a S-CVI of more than .93; and (c) coverage of the items based on the Year Four and Year Five Mathematics content and learning standards with a S-CVI of 1.00 except the items in subtopic of ‘Division of Time’. Further, the assignments of level to each option of the OMC items were judged to be appropriate by the two psychometric experts